Structural Behaviour of Precast Lightweight Foamed Concrete Sandwich Panel under Axial Load: An Overview - Samsudin, Suryani; Mohamad, Noridah (International Journal of Integrated Engineering, 2013)
The development of precast sandwich concrete has gained acceptance worldwide in conjunction with the Industrial Building System (IBS). The advancement and improvement of using wall panel has gone through a lot of achievements through the last decade. The usage of precast lightweight sandwich panel has become the alternative to conventional construction using brick wall. The usage of this panel system contributes to a sustainable and environmental friendly construction. This paper presents an overview of the latest development in precast concrete sandwich panel as an IBS. The purpose of this paper is to provide comprehensive information on latest research development of sandwich panel for building construction purposes. The information on sandwich panel’s composition, material, properties, strength, availability, and its usage as structural element are reported. An innovative concept used in the design of these systems and the use of lightweight materials is also discussed.